Comparative nonempirical analysis of emission properties of the Ar–MeIn glow discharge (Me = Ga, Zn, Sn, In, Bi, Tl). (16th April 2015) - Deminsky, M; Adamson, S; Chernysheva, I; Dyatko, N; Eletzkii, A; Kochetov, I; Napartovich, A; Rykova, E; Sukhanov, L; Umanskii, S; Zaitsevskii, A; Smith, D J; et al.
Abstract: A screening procedure is applied for several candidates (GaI3, ZnI2, SnI2, InI, BiI3, TlI) in respect of their light emission properties in a Ar–MeI n glow discharge. Candidates are compared in terms of emission efficiency for a wide range of external conditions: temperature, matrix gas pressure, and MeI n vapor pressure. The differences among the systems are explained by analyzing the kinetic mechanisms of formation, excitation, and loss of the emitting atoms. Analysis of the trends in the electronic structures of emitters (atoms) and precursors (molecules), as well as the stoichiometry and endothermicity of the plasma-chemical reactions, was made, and matched with selection rules.